Social Media Moderation Model on Entrepreneurial Intention among Students in Indonesia and Thailand - Fitri Fitri; Mutiarini Mutiarini; Giri Dwinanda; Chalog Tubsre; Pratanna Srisuk (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
The rapid development of digital technology has transformed how students access information and develop entrepreneurial opportunities, with social media emerging as a key platform influencing entrepreneurial motivation. However, limited studies have examined its role as a moderating factor in strengthening entrepreneurial intention among university students. This study aims to analyze the influence of entrepreneurial mindset and educational support on entrepreneurial intention, with social media as a moderating variable. A quantitative approach was employed using survey data from 251 university students in Indonesia and Thailand (response rate: 78.4%), analyzed using moderation regression and t-tests in IBM SPSS Statistics. The results indicate that entrepreneurial mindset (? = 0.163; p = 0.008) and perceived education (? = 0.179; p 0.001) have significant positive effects on entrepreneurial intention, while social media shows the strongest influence (? = 0.400). The model demonstrates strong explanatory power (R² = 0.780; adjusted R² = 0.703) and is statistically significant (F = 197.912; p 0.001). Furthermore, social media significantly moderates both relationships, highlighting its strategic role in enhancing entrepreneurial intention and supporting the integration of social media-based learning in entrepreneurship education.